2018
DOI: 10.1093/ibd/izy222
|View full text |Cite
|
Sign up to set email alerts
|

Starting Young: Trends in Opioid Therapy Among US Adolescents and Young Adults With Inflammatory Bowel Disease in the Truven MarketScan Database Between 2007 and 2015

Abstract: Sustained chronic opioid use in adolescents and young adults with IBD is increasingly common, underscoring the need for screening and intervention for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…These are particularly promising findings as children and young adults with IBD are a high-risk population. Research has shown that children with IBD experience higher rates of psychiatric disorders compared to healthy children and those with other chronic illnesses [ 5 , 6 ], increasing rates of chronic abdominal pain and chronic opioid use [ 42 , 43 , 44 ], and lower quality of life [ 5 , 6 ], all of which can negatively impact emotional and physical functioning in adulthood. As a result, there has been an increased call for behavioral interventions to support psychological and physical wellbeing among children with IBD [ 6 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are particularly promising findings as children and young adults with IBD are a high-risk population. Research has shown that children with IBD experience higher rates of psychiatric disorders compared to healthy children and those with other chronic illnesses [ 5 , 6 ], increasing rates of chronic abdominal pain and chronic opioid use [ 42 , 43 , 44 ], and lower quality of life [ 5 , 6 ], all of which can negatively impact emotional and physical functioning in adulthood. As a result, there has been an increased call for behavioral interventions to support psychological and physical wellbeing among children with IBD [ 6 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, and in line with former studies [21,22], the present study revealed increased postoperative overall morbidity and prolonged length of hospital stay in patients with Crohn's disease. Potential explanations for these findings include increased opioid use [23,24] and unfavourable baseline conditions with emergent or expedited procedures [25] in this particular subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that the prevalence of opioid use in IBD is rising, as it is the general United States population. 24 In a landmark paper, Targownik, et al investigated heavy opioid use in IBD patients and reported that individuals with IBD are 3 times more likely to become heavy opioid users compared with their matched controls. Heavy opioid use was also significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%